2011
DOI: 10.1080/1065657x.2011.10736977
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutrients Released from Phosphorus-Enriched Empty Oil Palm Fruit Bunches As Growing Media UsingSetaria splendida

Abstract: The use of oil palm empty fruit bunch, an agricultural waste from oil palm plantations, as a feeding material for earthworms during composting provides an alternative source of nutrients for plants. Information regarding the ability of earthworms in processing phosphorus-enriched empty oil palm fruit bunch and their effects on plants is still lacking. The objective of this study was to compare the effects of phosphorus-enriched empty oil palm fruit bunches applied as fresh, composted or vermicomposted media in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…A similar result was reported by Sabrina et al (2011) who confirmed that phosphorus enriched compost resulted in better growth and nutrient uptake by Setaria splendida.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A similar result was reported by Sabrina et al (2011) who confirmed that phosphorus enriched compost resulted in better growth and nutrient uptake by Setaria splendida.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, there are few reports (Biswas & Narayanasamy 2006;Sabrina et al 2011) regarding the use of P enriched compost to substitute for peat either partially or wholly. Organic nursery producers could save additional costs for fertilizers allowed in organic farming by using P enriched compost.…”
Section: Introductionmentioning
confidence: 84%
“…Earthworms have ability to increase plant development by enhancing the physical characteristics (Baker, 1999) and chemical conditions (Tuffen et al 2002;Sabrina et al 2009a;2011) of the soil, so they are important elements of rhizosphere ecosystem. Earthworms use the large part of organic wastes such as crop wastes, animal manure, biosolids and industrial wastes (Chan and Griffiths 1988;Hartenstein and Bisesi 1989;Edward 1998).…”
Section: Intrоduсtiоnmentioning
confidence: 99%
“…However, the total nitrogen content of the EFB fine particles was significantly higher (p<0.05) than the coarse particles (1.8, and 1.6 %, respectively). Nahrul Hayawin et al 2010 Table 5 shows the characteristics of vermicomposted EFB, non-vermicomposted (naturally composted) EFB, and non-composted (fresh) EFB treated with Gafsa rock phosphate (Sabrina et al, 2011). The nutrient contents of the EFB increased in the order of vermicompost>non-vermicompost>fresh.…”
Section: Compostmentioning
confidence: 99%